Kajian Perencanaan Komprehensif Digital dalam Meningkatkan Penjualan pada CV. Sahaja - Mufidah Fikri Amaliyah; Agus Hermani; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2022)
Intense market competition and a shrinking market make companies need the right marketing strategy to create high sales. The pandemic conditions and technological advances have made digital media one of the great opportunities to help companies get high sales. Therefore, comprehensive planning in digital marketing becomes quite important and needs to be designed properly. This study aims to analyze the planning of digital marketing strategies in increasing sales. The analysis was carried out by comparing the suitability of CV. Sahaja's digital marketing strategy planning with the SOSTAC strategy planning method. The results of the study showed that CV. Sahaja has not done comprehensive planning in digital marketing well based on the SOSTAC, digital marketing comprehesive planning method, (situation analysis, objectives, strategy, tactics, action, and control).Persaingan pasar yang ketat dan mengecilnya pasar menjadikan perusahaan memerlukan strategi pemasaran yang tepat untuk menciptakan penjualan yang tinggi. Kondisi pandemi dan kemajuan teknologi menjadikan media digital menjadi salah satu peluang besar untuk membantu perusahaan memperoleh penjualan yang tinggi. Oleh karena itu, perencanaan secara menyeluruh dalam pemasaran digital menjadi hal yang cukup penting dan perlu dirancang dengan baik. Penelitian ini bertujuan menganalisa tentang perencanaan strategi pemasaran digital dalam meningkatkan penjualan. Analisa dilakukan dengan membandingkan kesesuaian perencanaan strategi pemasaran digital CV. Sahaja Hasil dari penelitian menunjukkan bahwa CV. Sahaja belum melakukan pemasaran digital dengan baik berdasarkan pada metode perencanaan komprehensif pemasaran digital SOSTAC (situation analysis, objective, strategy, tactics, action, dan control).